Failures in dental prosthesis: dentists perception of the involved legal aspects (Acta Scientiarum. Health Sciences, 2014)
http://dx.doi.org/10.4025/actascihealthsci.v36i1.16851This aim of this study was to verify the level of knowledge of prosthodontics specialists from the city of Porto Alegre, Rio Grande do Sul State, concerning the failures of prosthetic works, and to provide a reflection on the type of responsibility assumed by the prosthodontist during the dental treatment. This was a descriptive cross-sectional study with a non-probabilistic sample, conducted through questionnaires with closed and open questions. The data was analyzed using the Fisher’s Exact Test (p value < or = 0.005). The sample consisted of 143 questionnaires. The statistical analysis evidenced that the dentists with up to 15 years of professional practice assign the responsibility of failures most often to the laboratory (p = 0.001) and to the patient (p = 0.021), but over the years this trend is reversed. The prosthodontists included in the study proved to have an adequate knowledge of issues that pervade the failures in the prosthodontics specialty. In relation to the parameters of the professional responsibility, it is necessary to consider the type of duty assumed by the prosthodontist as for the responsibility of means.